csaluja wrote:
chetan2u wrote:
Karthik200 wrote:
\((1 + \sqrt{3})\sqrt{(2 + [square_root]3})[/square_root]\)
A. \(\sqrt{2}(2 - \sqrt{3})\)
B. \(\sqrt{2}(2 + \sqrt{2})\)
C. \(\sqrt{2}(2 + \sqrt{3})\)
D. \(\sqrt{2}(3 + \sqrt{3})\)
E. \(\sqrt{3}(2 + \sqrt{3})\)
Guys, sorry for the poor question formatting. I tried my best to make it proper. However, the square root inside the square root is somehow not appearing properly. Kindly, use the attachment to view the question.
Let x be the value of the equation..
\(X=(1+√3)(\sqrt{2+√3})\)...
So \(x^2=(1+3+2√3)(2+√3)=(4+2√3)(2+√3)=2(2+√3)(2+√3)=2(2+√3)^2\)..
Therefore x=√2*(2+√3)
C
Hi Chetan,
I was wondering could you please explain how you went from 2(2+√3)^2 to √2*(2+√3)? Would greatly appreciate it!
Hi
csaluja,
Here \(x^2=2*(2+√3)^2\) (I hope you are clear till this point)
Taking square root both sides, we have
\(\sqrt{x^2}=\sqrt{2*(2+√3)^2}=\sqrt{2}*\sqrt{(2+√3)^2}\)
(You know \(\sqrt{a*b}=\sqrt{a}*\sqrt{b}\))
Or, \(x=\sqrt{2}*(2+√3)\)
Hope it helps.
_________________
Regards,
PKN
Rise above the storm, you will find the sunshine